Relationship between entrepreneurship education and entrepreneurial goal intentions: psychological traits as mediators - Takawira Munyaradzi Ndofirepi (Journal of Innovation and Entrepreneurship, 2020)
Despite the commonly held view that entrepreneurship education and training nurtures future entrepreneurs, little is known about the mechanism through which this intervention impacts on its intended outcomes. The purpose of this study was to test if selected psychological traits (need for achievement, risk-taking propensity, internal locus of control) mediated the predictive relationship between the perceived effects of entrepreneurship education and entrepreneurial intentions. A crosssectional survey of a sample of 308 vocational education students in Zimbabwe was used for this purpose. The results show that the effects of entrepreneurship education variable had a positive and statistically significant relationship with need for achievement, risk-taking propensity, internal locus of control and entrepreneurial goal intentions. Moreover, need for achievement, risk-taking propensity and internal locus of control accounted for a statistically significant amount of variance in entrepreneurial intentions. However, of the three psychological traits, only need for achievement partially mediated the relationship between the effects of entrepreneurship education and entrepreneurial goal intentions. The outcome has implications on the design and focus of entrepreneurship education programmes.
Keywords: 650; Entrepreneurship education; Entrepreneurial intention; Need for achievement; Risk-taking propensity; Locus of control